2018
DOI: 10.2147/ppa.s165357
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice on and willingness to pay for human papillomavirus vaccine: a cross-sectional study in Hanoi, Vietnam

Abstract: BackgroundDespite its effectiveness in preventing human papillomavirus (HPV) infection, the rate of uptake of the HPV vaccine is low in Vietnam. This study aimed to investigate barriers related to knowledge–attitude–practice (KAP) about the HPV vaccine and willingness to pay (WTP) for the vaccine among those using services in an urban vaccination clinic in Hanoi, Vietnam.Materials and methodsA cross-sectional study was conducted in a vaccination clinic of the Institute for Preventive Medicine and Public Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 34 publications
(33 reference statements)
6
22
2
1
Order By: Relevance
“…The uptake rate of HPV immunization in developing countries remains comparatively low. 15 , 16 The HPV vaccine uptake rate in Vietnam (31.8%) 17 was higher than previously reported (2.3%), 18 however lower than China (47.2%) and for European countries such as Germany (53%) 19 and the Netherlands (49.9%). 20 A three-shot series of the vaccine in Vietnam costs from $150–$195 which is comparatively low compared to the global average of $400.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The uptake rate of HPV immunization in developing countries remains comparatively low. 15 , 16 The HPV vaccine uptake rate in Vietnam (31.8%) 17 was higher than previously reported (2.3%), 18 however lower than China (47.2%) and for European countries such as Germany (53%) 19 and the Netherlands (49.9%). 20 A three-shot series of the vaccine in Vietnam costs from $150–$195 which is comparatively low compared to the global average of $400.…”
Section: Introductionmentioning
confidence: 75%
“…A limitation was that participants were not queried specifically about how much parents could pay for an HPV vaccination if an HPV vaccine would be available for boys, when cost was sometimes identified as a barrier and the vaccine costs for girls are still high, especially when compared to personal incomes in Vietnam. 17 HPV vaccination for men also faces some issues from a communication perspective with low levels of public health awareness, lack of proven effectiveness, and stigmatized perceptions of many people regarding the HPV vaccine. 17 …”
Section: Limitations Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Only the price of the vaccine had a significant effect on willingness to vaccinate, which is consistent other surveys. 17 Studies have shown that physician recommendation is an important and consistent predictor of vaccine uptake. 18 Astudy in New Zealand reported that 96.5% of health workers agreed or strongly agreed that they would recommend the HPV vaccine, compared to just 63% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Only the price of the vaccine had a significant effect on willingness to vaccinate, which is consistent other surveys. 17 …”
Section: Discussionmentioning
confidence: 99%